Changes in the genetic variability of the Furioso-North Star population between 1989 and 2019 - Klein, Renáta; Oláh, János; Mihók, Sándor; Posta, János (Acta Agraria Debreceniensis, 2022)
The Furioso-North Star (FNS) is one of the indigenous Hungarian horse breeds, originated from Mezőhegyes Stud. The aim of this work was to analyze the pedigree diversity and inbreeding of the registered Hungarian Furioso-North Star population in two different time points: the first was the active population in 1989, the second was the active population in 2019. Pedigree data was analyzed using Endog 4.8 software. The pedigree completeness was calculated in three different ways. In the past 30 years the pedigrees became more complete. In the population 2019 were 5 horses with ancestor in the 40th generation. Only 17–17 animals covered the 50% of the genetic variability for the two population. The most important ancestor was Herod xx in both reference populations. The FNS breed has English Thoroughbred background, that might be the reason of having several horses form this breed in the database. There were six animals among the ten most important ancestors in both reference populations. The average inbreeding coefficient was 3.31 in 1989 and 4.22 in 2019. Animals with highest inbreeding coefficient were born from the mating of close relatives (typically father-daughter). The Bart Furioso III-84 Boglár had the highest inbreeding coefficient (0.299) in the population 2019.